Rimsky-Korsakov and His World - Frolova-Walker, Marina (Book collections on Project MUSE., 2018)
During his lifetime, Nikolai Rimsky-Korsakov (1844-1908) was a composer whose work had great influence not only in his native Russia but also internationally. While he remains well-known in Russia-where many of his 15 operas and various orchestral pieces are still in the standard repertoire - very little of his work is performed in the West today beyond 'Scheherezade' and arrangements of The 'Flight of the Bumblebee'. In Western writings, he appears mainly in the context of the Mighty Handful, a group of five Russian composers to which he belonged at the outset of his career. This text finally gives the composer centre stage and due attention. In this work, Rimsky-Korsakov's major operas, 'The Snow Maiden', 'Mozart and Salieri', and 'The Golden Cockerel', receive multifaceted exploration and are carefully contextualized within the wider Russian culture of the era.